Airway clearance therapy in cystic fibrosis patients - Pisi, G.; Chetta, A. (Acta Biomedica Atenei Parmensis, 2009)
Cystic fibrosis (CF) is the most common life-shortening inherited disease affecting Caucasian people. In CF, the major feature of lung disease is the retention of mucus due to impaired clearance of abnormally viscous airway secretions. Airway clearance techniques (ACTs) may significantly improve mucociliary clearance and gas exchange, thereby being of clinical benefit in reducing pulmonary complications in CF patients. ACTs include conventional chest physiotherapy, active cycle of breathing techniques, autogenic drainage, positive expiratory pressure and high-frequency chest compression. In order to suit the needs of patients, families and care-givers, ACTs need to be individually and continuously adapted.